Crystallographic studies of multimeric and ancestral haloalkane dehalogenases - Mazur, Andrii (Jihočeská univerzita, 2023)
ANNOTATIOIN Halogenated pollutants represent one of the greatest threats to nature. Scientists have been searching for a solution to degradation of such compounds and soil remediation for many years, and several suggestions have been completed until know. One of the ways is the biodegradation of halogenated compounds by bacterial enzymes, such as haloalkane dehalogenases, enzymes that cleave halogen bonds and degrade this kind of compounds. The wide substrate specificity of these enzymes pushes forward the research for new techniques to improve existing dehalogenases and revealing new features in unique properties of novel types. In this work, X-ray crystallographic analysis was successfully used for structural-functional characterization of novel isolated and engineered haloalkane dehalogenases. The first part is devoted to the characterization of the novel haloalkane dehalogenase DpaA from Paraglaciecola agarilytica NO2. Unusual feature of this enzyme is its property to form multimeric construction, whereas other members of the same phylogenetic subfamily are present as monomers. We aim to expand the knowledge of the structure and formation of the multimeric haloalkane dehalogenases. The second part of the thesis deals with novel enzyme synthesized by use of the ancestral sequence reconstruction from dehalogenases with the broadest range substrate specificity LinB and DmbA. Armed with a new technique the novel synthesized enzyme can enhance the effectiveness of the degradation of halogenated environmental pollutants.
Crystallographic studies of multimeric and ancestral haloalkane dehalogenases
Crystallographic studies of multimeric and ancestral haloalkane dehalogenases
Keywords: X-Ray crystallography; protein crystallization; haoalkane dehaogenases; multimeric enzymes; ancestral structure reconstruction.; X-Ray crystallography; protein crystallization; haoalkane dehaogenases; multimeric enzymes; ancestral structure reconstruction.